Permainan Matematika Online Beads on String untuk Belajar Matematika yang Bermakna dan Menyenangkan di Madrasah Ibtidaiyah (MI) - Dewi Hamidah; Zun Azizul Hakim (Cendekia: Kependidikan dan Kemasyarakatan, 2016)
Many people think that mathematics is a scary subject especially among children. Therefore, mathematics should be taught with a good and fun way. One of the good and fun approaches is through games. The development of internet technology has offered a wide range of facility, especially on websites that provide online math games. One of them is free online game “Bead on String”. This paper is intended to describe the connection of free online game “Beads on String”, with the materials of the integer division with a remainder and no remainder that is taught at school. The result of the analysis to free online games “Bead on String” indicates that the game can be used to build an understanding of learning concepts “Pembagian bilangan bulat bersisa dan tak bersisa (Integer division with a remainder and no remainder)”.ظنّ كثير من الناس أن الرياضيّات علم صعبٌ ومخيف، وخاصة الصغار. بهذا لابد أن يُدرّس هذا العلم بطريقة جيّدة ومريحة. وأحد المداخل لتدريس هذا العلم عن طريق الألعاب. وبتطوّر تكنولوجيا الشبكة الدولية توجد هناك الوسائل وخاصة موجودة في المواقع على الانترنيت المُعدّة لألعاب الرياضيّات.  ومن هذه الألعاب يسمّى ب " Bead on String”". حاولت هذه المقالة عرض العلاقة بين لعب " Bead on String”"  أون لين المجّاني وبين عدد صحيح ذي بقية وعدد صحيح ليس له بقية التي تُدرّس في المدارس. دلّت نتائج البحث على أن  هذا النوع من اللعب يُمكن استخدامه لبناء الفهم عن مفهوم التعليم عن " تقسيم العدد الصحيح ذي بقية والعدد الصحيح ليس له بقية "